TỐI ƯU THÔNG SỐ LÊN MEN SINH TỔNG HỢP α-L-RHAMNOSIDASE BỞI Aspergillus niger ĐH51 SỬ DỤNG PHƯƠNG PHÁP ĐÁP ỨNG BỀ MẶT - Đinh, Thị Thu Trang; Nguyễn, Thi Hoài; Đỗ, Tất Thịnh; Lê, Thị Huệ; Vũ, Thị Hạnh Nguyên (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
OPTIMIZATION OF FERMENTATION PARAMETERS FOR PRODUCTION α-L-RHAMNOSIDASE BY ASPERGILLUS NIGER ĐH51 USING RESPONSE SURFACE METHODOLOGY The Response Surface Methodology (RSM) was used to optimize the fermentation condition for the production of α-L-rhamnosidase by Aspergillus niger ĐH51. RSM reflects the interaction and impact of different variables at a given moment. Among 11 surveyed factors by Plackett-Burman design, the concentrations of rhamnose, rutin, and pH were identified as the 3 most influencing factors on the αLrhamnosidase production (p < 0.05). The optimal conditions derived from BoxBehnken design were: rhamnose = 1.1%, rutin = 0.6% and pH = 5.7. Under this condition, the highest α-L-rhamnosidase activity obtained was 3.67 U/ml. When switching to fermentation in the Winpact 10 L fermentor, α-L-rhamnosidase activity of 3.85 U/ml was obtained at an agitation speed of 200 rpm and aeration rate of 0.8 vvm.